2015
DOI: 10.1017/s0952523815000280
|View full text |Cite
|
Sign up to set email alerts
|

GlyRα2, not GlyRα3, modulates the receptive field surround of OFF retinal ganglion cells

Abstract: Receptive fields (RFs) of most retinal ganglion cells (RGCs) consist of an excitatory center and suppressive surround. The RF center arises from the summation of excitatory bipolar cell glutamatergic inputs, whereas the surround arises from lateral inhibitory inputs. In the retina, both gamma amino butyric acid (GABA) and glycine are inhibitory neurotransmitters. A clear role for GABAergic inhibition modulating the RGC RF surround has been demonstrated across species. Glycinergic inhibition is more commonly as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…However, the biological roles of other GlyR subtypes, containing the α2, α3 and α4 subunits, are still under investigation. Knockout mice have revealed roles for GlyR α2 in retinal rod photoreceptor development, crossover inhibition and the receptive field surround of “off” retinal ganglion cells (Young and Cepko, 2004 ; Nobles et al, 2012 ; Zhang C. et al, 2015 ). GlyR α2 also appears to modulate ethanol consumption, since knockout mice show reduced ethanol intake and preference in the two-bottle choice test (Blednov et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the biological roles of other GlyR subtypes, containing the α2, α3 and α4 subunits, are still under investigation. Knockout mice have revealed roles for GlyR α2 in retinal rod photoreceptor development, crossover inhibition and the receptive field surround of “off” retinal ganglion cells (Young and Cepko, 2004 ; Nobles et al, 2012 ; Zhang C. et al, 2015 ). GlyR α2 also appears to modulate ethanol consumption, since knockout mice show reduced ethanol intake and preference in the two-bottle choice test (Blednov et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…GlyR α2 is also pivotal in the modulation of ethanol intake, aversion and preference (Blednov et al, 2015), retinal photoreceptor development (Young and Cepko, 2004) and the control of receptive field surround in retinal ganglion cells (Nobles et al, 2012; Zhang C. et al, 2015). However, more recent studies using a novel Glra2 knockout line provided compelling evidence that extrasynaptic activation of GlyRs containing the α2 subunit in interneurons is vital for control of cortical tangential migration during embryogenesis (Avila et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this, non-synaptic taurine or glycine release onto GlyRs was found to be vital for neocortical and spinal cord development (Flint et al, 1998;Scain et al, 2010). Studies using Glra2 knockout mice have since revealed pivotal roles for GlyR α2 in retinal photoreceptor development (Young and Cepko, 2004) and the control of receptive field surrounds in retinal ganglion cells (Nobles et al, 2012;Zhang et al, 2015a), as well as modulation of ethanol intake, aversion and preference (Blednov et al, 2015;San Martin et al, 2020;Araya et al, 2021). However, a major role for GlyR α2 has been identified in dorsal cortical progenitor homeostasis and cortical interneuron migration (Avila et al, 2013(Avila et al, , 2014.…”
Section: Introductionmentioning
confidence: 71%